2014
DOI: 10.3109/10903127.2013.864359
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Sensitivity of Emergency Medical Service Impression of Stroke

Abstract: Stroke was missed more frequently when CPSS was not documented, in patients without motor signs, and in patients with moderate-severe stroke. The sensitivity of prehospital screening for patients with moderate-severe stroke might be improved by including additional non-motor signs and by stressing indications for when screens should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
4
18
0
Order By: Relevance
“…Other factors associated with EMS sensitivity were early presentation (OR, 2.22) and increasing NIHSS (OR, 1.09 for each 1 point increase). These findings have also been described previously 18 and suggest that paramedics are more likely to recognize patients with more obvious stroke presentations or those perceived to be possible candidates for tPA therapy. An emergency dispatcher impression of possible stroke was also associated with a marginally significant increased likelihood of accurate EMS provider stroke recognition in the multivariable analysis (OR, 1.94).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Other factors associated with EMS sensitivity were early presentation (OR, 2.22) and increasing NIHSS (OR, 1.09 for each 1 point increase). These findings have also been described previously 18 and suggest that paramedics are more likely to recognize patients with more obvious stroke presentations or those perceived to be possible candidates for tPA therapy. An emergency dispatcher impression of possible stroke was also associated with a marginally significant increased likelihood of accurate EMS provider stroke recognition in the multivariable analysis (OR, 1.94).…”
Section: Discussionsupporting
confidence: 64%
“…A recent meta-analysis of 3 validation studies of the CPSS found sensitivities ranging from 79% to 95% 15 ; however, a recently published study conducted in New York demonstrated EMS sensitivity of only 50% despite CPSS education and incorporation into local stroke protocols. 18 In our cohort of EMS-transported cases, EMS sensitivity for stroke recognition was 74%, slightly lower than the observed range in previous CPSS validation studies. 15 Furthermore, PPV of EMS suspicion of stroke was only 52%, suggesting that there is opportunity for improvement by reducing both the over-and under-recognition of stroke by EMS providers.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Results from previous studies addressing the issue of ACE mimics are not uniform. The most frequent misdiagnoses have included seizures (7-21%), vertigo (2-5%), brain tumours (4-15%), metabolic and electrolyte disturbances (4-24%), infections (7-16%) and functional disorders (1-8%), which only partially overlap with our results (vertigo followed by metabolic and electrolyte disturbances, headache, seizures and brain tumours without any functional disorders) [10,11,[26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 72%
“…A study published by Gropen et al found that EMS had the lowest sensitivities in stroke diagnosis in both the lower and higher NIHSS scores. They also found that EMS had greatest difficulty in diagnosing stroke when nonmotor signs predominated including aphasia and neglect [22]. In another study, the most common EMS impressions on missed strokes included generalized weakness, altered mental status, or dizziness.…”
Section: Stroke Recognition By Ems Providersmentioning
confidence: 96%